Nonlinear modeling of concentrically loaded reinforced blockwork masonry columns - Köksal, HO; Doran, B; Ozsoy, AE; Alacali, SN (CANADIAN SCIENCE PUBLISHING, 2004)
Since only a limited number of experimental and analytical studies have been carried out for the purpose of developing strength design procedures for reinforced blockwork masonry columns, there is a certain need for further studies that reflect material properties and behavior of blockwork masonry more closely. This paper deals with a non-linear finite element modeling of the concentrically loaded reinforced blockwork masonry columns making use of both elasto-plastic and isotropic damage models. If the damage model is enriched with the introduction of a simple relation for the material damage parameter that accounts for the mesh size effect, three-dimensional finite element analyses of columns for the well-known experimental works in the literature are accomplished. Finally, the predictions from both the numerical analyses and the existing expressions for the ultimate load of the masonry columns are compared with the experimental results.
Keywords: compressive strength; reinforced blockwork masonry column; finite element method; Drucker-Prager yield criterion; isotropic damage theory; CONCRETE; BEHAVIOR; Engineering